Enhancing Business Continuous Improvement Using TCI Model - Fazali Ghazali, Mohamad; Saad., Rohaizah (International Journal of Engineering and Technology, 2019)
Since the current world global economy has become competitive, most of the manufacturing industries are trying to improve productivity by adopting technology and spur the innovation such as quality improvement tools and technique. The most effective way to improve productivity is by establishing an Innovative Creative Circle as a problem-solving team to enhance manufacturing processes by reducing waste, and improving customer needs and quality of the product or services. By integrating Innovative Creative Circle with appropriate problem solving tools such as TRIZ methodology, the company is able to eliminate most of the unnecessary cost that will affect the operation cost, the products and the processes of the organizations. This paper provides a case study of an activity of TCI Model as part of continuous improvement tools and creatively solve daily problems including impossible-to-solve problems. TCI Model has succeeded in improving the quality of products or services with a lower cost operation. Hence, this has given a competitive advantage over other businesses.Â